Observed secular gravity trend at Onsala station with the FG5 gravimeter from Hannover - Timmen, L.; Engfeldt, A.; Scherneck, H.-G. (Berlin, Boston : De Gruyter, 2015)
Annual absolute gravity measurements with a FG5 instrument were performed in Onsala Space Observatory by the Institute of Geodesy of the Leibniz Universität Hannover from 2003 to 2011 and have been continued with the upgraded meter FG5X in 2014. Lantmäteriet, Gävle, with their FG5 absolute gravimeter have visited Onsala since 2007. Because small systematic errors may be inherent in each absolute gravimeter, their measuring level and a resulting bias (offset) between the instruments must be controlled over time by means of inter-comparison. From 2007 to 2014, 8 direct comparisons took place well distributed over the time span. A complete re-processing of the absolute gravity observations with the Hannover instrument has been conducted to improve the reduction of unwanted gravity effects. A new tidal model is based on continuous time series recorded with the GWR superconducting gravimeter at Onsala since 2009. The loading effect of the Kattegat is described with a varying sea bottom pressure (water and air mass load) and has been validated with the continuous gravity measurements. For the land uplift,which is a result of the still ongoing glacial isostatic adjustment in Fennoscandia, a secular gravity trend of −0.22 μGal/yr was obtained with a standard deviation of 0.17 μGal/yr. That indicates a slight uplift but is still not significantly different from zero.